2001
DOI: 10.1128/jvi.75.6.3048-3052.2001
|View full text |Cite|
|
Sign up to set email alerts
|

Gender Influences Herpes Simplex Virus Type 1 Infection in Normal and Gamma Interferon-Mutant Mice

Abstract: Gender influences the incidence and severity of some bacterial and viral infections and autoimmune diseases in animal models and humans. To determine a gender-based difference, comparisons were made between male and female mice inoculated with herpes simplex virus type 1 (HSV-1) by the corneal route. Mortality was higher in the male mice of the three strains tested: 129/Sv//Ev wild type, gamma interferon (IFN-␥) knockout (GKO), and IFN-␥ receptor knockout (RGKO). Similarly, in vivo HSV-1 reactivation occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
63
4

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 38 publications
14
63
4
Order By: Relevance
“…71 Male IFNg or IFNg receptor knockout mice infected with herpes simplex virus type-1 have a higher frequency of reactivation and a higher associated mortality than wild-type mice, whereas there is no difference between knockout and wild-type females. 72 Taken together with previous studies, our study provides further evidence that there is an association between IFNG polymorphisms and susceptibility to sporadic MS. Genetic variation in IFNg may in part account for gender differences in susceptibility to MS.…”
Section: Discussionsupporting
confidence: 86%
“…71 Male IFNg or IFNg receptor knockout mice infected with herpes simplex virus type-1 have a higher frequency of reactivation and a higher associated mortality than wild-type mice, whereas there is no difference between knockout and wild-type females. 72 Taken together with previous studies, our study provides further evidence that there is an association between IFNG polymorphisms and susceptibility to sporadic MS. Genetic variation in IFNg may in part account for gender differences in susceptibility to MS.…”
Section: Discussionsupporting
confidence: 86%
“…1E). Furthermore, the higher relative resistance of adult female mice to HSV-1 infection is noted in the literature (33)(34)(35) and is consistently supported in our empirical studies (unpublished observations). Our data provide compelling evidence that the sex bias in susceptibility could be mechanistically linked to a disparity in antiviral gene induction during acute infection.…”
supporting
confidence: 77%
“…These discrepancies may be due to different animal strains, different virus strains or different animal models. We have shown that the effect of LAT on the HSV-1 latency-reactivation phenotype is mouse strain dependent , whereas others have reported a gender bias (Han et al, 2001). …”
Section: Discussionmentioning
confidence: 99%